A inferência na compreensão de leitura de textos jornalísticos - Tacini, Renata Ferreira (2010)
With the purpose of analyzing the comprehension of joumalistic texts of the reportage genre, by students from High School of a Public School of São Paulo State, the inferential process was taken a basis, as an activity capable of activating knowledge of several provenances contributing for the production of senses in the reading. The methodological guidance was ruled by socio-cognitive interacionist studies which made possible to investigate how social, cultural and interactional aspects interfere in the comprehension of texts which, naturally, do not bring in itself everything that is needed to understand it. The reading was assumed as a process in which the reader performs an active work of comprehension and interpretation, from its objectives, its knowledge about the subject, about the language, about the text support and it implies selection, anticipation, inference and verification. The production analysis of inferences aimed to demonstrate the reader's role as active subject capable of connecting ideas, concluding, deducing, and creating hypothesis from the explicit information in the written text. In the empirical work a sequence of reading was elaborated which revealed thç:'inferential process of the students in the reading of the text "Brazilian miss 13 years due to sickness". The result showed that the inferences production allowed the students to relate social, political and economical issues to the knowledge stored in memory, which IDade possible for them to extrapolate the limits of the personal experiences and perceive the reality of the public health not only in its social context, but in other realities